2020
DOI: 10.1101/2020.06.04.134379
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Zinc Finger Antiviral Protein restricts SARS-CoV-2

Abstract: 1Recent evidence shows that the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) 2 is highly sensitive to interferons (IFNs). However, the underlying antiviral effectors remain to be 3 defined. Here, we show that Zinc finger antiviral protein (ZAP) that specifically targets CpG 4 dinucleotides in viral RNA sequences restricts SARS-CoV-2. We demonstrate that ZAP and its 5 cofactors KHNYN and TRIM25 are expressed in human lung cells. Type I, II and III IFNs all 6 strongly inhibited SARS-CoV-2 and fur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 56 publications
(3 reference statements)
1
26
0
Order By: Relevance
“…After our work was posted on the bioarxiv, R. Nchioua and colleagues have shown the importance of ZAP in controlling the response against SARS-CoV-2, see [37], by demonstrating that a knock-out of this protein increases SARS-CoV-2 replication. This finding supports our prediction that recognition of SARS-CoV-2 by ZAP imposes a significant fitness cost on the virus, as demonstrated by its early evolution to remove ZAP recognition motifs.…”
Section: Discussionmentioning
confidence: 99%
“…After our work was posted on the bioarxiv, R. Nchioua and colleagues have shown the importance of ZAP in controlling the response against SARS-CoV-2, see [37], by demonstrating that a knock-out of this protein increases SARS-CoV-2 replication. This finding supports our prediction that recognition of SARS-CoV-2 by ZAP imposes a significant fitness cost on the virus, as demonstrated by its early evolution to remove ZAP recognition motifs.…”
Section: Discussionmentioning
confidence: 99%
“…ISGs positively potentiating IFN signaling, such as IFIH1/MDA5, TANK, IRF7, and STAT1, were also increased in the bronchoalveolar lavage fluid (BALF) of COVID-19 patients as compared with healthy controls [105] and could potentially contribute to the amplification of IFN-I response against SARS-CoV-2 replication. Zinc finger antiviral protein (ZAP), which is encoded by an ISG, contributes to the anti-SARS-CoV-2 effect of IFNs in human lung Calu-3 cells [114]. ZAP is known for restricting the replication of numerous viruses such as retroviruses and filoviruses [115].…”
Section: Detrimental Effects Of Ifns On Sars-cov-2 Replicationmentioning
confidence: 99%
“…Various host antiviral mechanisms accelerate the depletion of CpG dinucleotides (a cytosine followed by a guanine in the 5' to 3' direction) in virus genomes. This is thought to be primarily mediated either through selective pressures by a CpG-targeting mechanism involving the Zinc finger Antiviral Protein (ZAP) 42 or C to U hypermutation by APOBEC3 cytidine deaminases 43 , and recent work has demonstrated that the CpG binding ZAP protein inhibits SARS-CoV-2 replication in human lung cells 44 . These forces are likely to vary across tissues and between hosts.…”
Section: Patterns Of Cpg Depletion In the Ncov Clade Genome Compositmentioning
confidence: 99%